Case Report: Desmoglein-3 Gene Mutation Leading to Airway Compromise in Fraternal Twin Infants. Issue 4 (12th April 2022) - Bajwa, Jasmine; Deserres, Lianne; Lando, Tali; Salik, Irim
Abstract : The desmoglein 3 18q11 gene mutation has not been well described in humans, except for a few case reports. The desmoglein 3 gene controls a transmembrane component of the desmosome complex that mediates epidermal cell adhesion and integrity of the oropharyngeal mucosa. We present two fraternal twin infants who exhibited features of airway compromise and respiratory distress shortly after birth. These infants presented with chronic, cyclical sloughing of the upper airway, larynx, and pharynx associated with difficult airway management and eventual respiratory failure. It is imperative that practitioners be aware of the severity of this rare mutation.